DIVINE LOVE IN AL-HALLAJ’S SUFISM: A STUDY OF LOUIS MASSIGNON'S THOUGHT AND ITS RELEVANCE IN THE DIGITAL ERA - Joma, Muhammad Asmar; Subekti, Fiqi Restu (Jurnal Studi Islam, 2025)
The concept of divine love in the Sufism of al-Hallaj, as examined by Louis Massignon, holds particular significance in the context of comprehending the profundity of Islamic spirituality. A plethora of studies have hitherto concentrated on historical aspects or general Sufi practices, without critically linking al-Hallaj's thought to the contemporary digital context. The objective of this study is to address the shortcomings of previous studies by establishing a connection between al-Hallaj's thought and the dynamics of the digital age. The present research employs a qualitative approach through library research, utilising reference sources such as La Passion de Hallaj, Essai sur les Origines du Lexique Technique de la Mystique Musulmane, Kitab al-Tawasin, and Diwan al-Hallaj. The results of the study demonstrate that, in the context of al-Hallaj, the concept of divine love necessitates the complete dissolution of the self through the stages of fana (the elimination of the ego), baqa (soul purification), and hulul (union with God). Massignon interpreted al-Hallaj's experience of divine love as a form of mystical sacrifice equivalent to prophetic suffering. A comparison of the two reveals a divergence in their methodological approach: while al-Hallaj placed significant emphasis on direct experience, Massignon, as a Western Orientalist, employed a historical-phenomenological lens and drew parallels between this and Christian theology. The pertinence of divine love in the digital era is predicated on its capacity to elicit intrinsic awareness through the pursuit of existential significance. It is through this pursuit that digital ethics are cultivated, utilising a methodological framework that accentuates riyadah, tazkiyah an-nafs, and ontological deepening, thereby ensuring that its spiritual values are not diminished. Accordingly, al-Hallaj's divine love, as delineated by Massignon, constitutes the basis for authentic spiritual transformation. Key words: Louis Massignon, al-Hallaj’s Sufism, Divine Love, Digital Era.